Impact of sex on long‐term cardiovascular outcomes of patients undergoing percutaneous coronary intervention for acute coronary syndromes. Issue 4 (25th May 2021) - Roumeliotis, Anastasios; Claessen, Bimmer E.; Sartori, Samantha; Cao, Davide; Qiu, Hanbo; Camaj, Anton; Nicolas, Johny; Chandiramani, Rishi; Goel, Ridhima; Chiarito, Mauro; Torguson, Rebecca; Sweeny, Joseph; et al.
Abstract: Background: Women with acute coronary syndrome (ACS) generally present with more comorbidities and experience worse clinical outcomes compared with males. However, it is unclear whether this represents genuine sex‐related difference or stems from clinical, procedural and socioeconomic factors. Methods: We analyzed consecutive patients undergoing percutaneous coronary intervention (PCI) for ST‐segment elevation myocardial infarction (STEMI), non‐STEMI or unstable angina at a single tertiary‐care center. Exclusion criteria were unknown sex, age < 18 years and PCI with bare metal stent or without stent placement. The study population was stratified according to sex. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE) defined as the composite of death, spontaneous myocardial infarction, or stroke at 1 year. Secondary endpoints were individual components of MACCE, target vessel revascularization (TVR) and clinically significant bleeding. Results: Of the 7362 patients included, 5031 (68.3%) were men and 2331 (31.7%) women. Women were older and presented with a higher burden of comorbidities while men had more complex coronary anatomy. The incidence of 1 year MACCE was significantly higher among women (8.0% versus 5.6%; p  < 0.01) compared to men. Women also experienced a higher rate of bleeding (2.3% vs. 1.4%; p  = 0.02) while there were no differences between groups in terms of TVR (8.1% vs. 7.8%; p ‐value = 0.83). Differences in outcomes were attenuated after multivariable adjustment. Findings were consistent across ACS subgroups. Conclusions: In a contemporary ACS population treated with drug‐eluting stents, women experienced a higher crude rate of 1‐year MACCE. This was no longer apparent after accounting for baseline imbalances.